2013
DOI: 10.1093/cvr/cvt004
|View full text |Cite
|
Sign up to set email alerts
|

Translating cardioprotection for patient benefit: position paper from the Working Group of Cellular Biology of the Heart of the European Society of Cardiology

Abstract: Coronary heart disease (CHD) is the leading cause of death and disability worldwide. Despite current therapy, the morbidity and mortality for patients with CHD remains significant. The most important manifestations of CHD arise from acute myocardial ischaemia-reperfusion injury (IRI) in terms of cardiomyocyte death and its long-term consequences. As such, new therapeutic interventions are required to protect the heart against the detrimental effects of acute IRI and improve clinical outcomes. Although a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
203
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(207 citation statements)
references
References 146 publications
2
203
1
1
Order By: Relevance
“…Patients who survive the initial event could suffer significant morbidity and mortality due to adverse ventricular remodeling resulting in the long-term heart failure. Acute myocardial IRI is the major cause of the adverse effects of CHD on the myocardium [2]. Our results demonstrate that Intralipid ® indeed can protect the resulting injury in hearts due to IRI as shown by our in-vivo non-invasive multi-parameter CMRI in a rat model of acute myocardial infaction.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Patients who survive the initial event could suffer significant morbidity and mortality due to adverse ventricular remodeling resulting in the long-term heart failure. Acute myocardial IRI is the major cause of the adverse effects of CHD on the myocardium [2]. Our results demonstrate that Intralipid ® indeed can protect the resulting injury in hearts due to IRI as shown by our in-vivo non-invasive multi-parameter CMRI in a rat model of acute myocardial infaction.…”
Section: Discussionsupporting
confidence: 68%
“…Despite of the advancement of revascularization therapy and pharmacological thrombolysis, the long-term outcome of patients after acute myocardial infarction (MI) could be poor [1], due to myocardial ischemia-reperfusion injury (IRI) with resultant cardiomyocyte death and adverse long-term consequences [2] [3]. The abrupt restoration of circulation in the infarct-related artery not only brings in the much needed oxygen and nutrients, but also triggers inflammation and oxidative stress, which may cause greater damage to the tissue, and the subsequent adverse myocardial remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our and previous observations,6 Małek et al did not report any difference in LVEF. The importance of measuring area at risk in addition to infarct size has previously been emphasized given that area at risk has an impact on infarct size 30. Given that infarct size, myocardial salvage index, LVEF, LVH, and MVO are associated with adverse outcome in STEMI patients,20, 22, 31, 32, 33 findings in the present study indicate that the impaired prognosis in patients with acute MI and LVH may directly be attributed to more‐extensive myocardial damage and smaller salvage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results from longitudinal human studies have not provided a uniform picture of the efficacy and safety of IPoC 8. In 2013 a single‐center study by Freixa et al showed rather a significant deterioration in the myocardial salvage and the myocardial salvage index along with reduced pump function 6 months after myocardial ischemia 9.…”
Section: Introductionmentioning
confidence: 99%